Lipid-based liquid crystalline materials in electrochemical sensing and nanocarrier technology - Zatloukalova, Martina; Poltorak, Lukasz; Bilewicz, Renata; Vacek, Jan (Mikrochimica acta, 2023)
Some biologically active substances are unstable and poorly soluble in aqueous media, at the same time exhibiting low bioavailability. The incorporation of these biologically active compounds into the structure of a lipid-based lyotropic liquid crystalline phase or nanoparticles can increase or improve their stability and transport properties, subsequent bioavailability, and applicability in general. The aim of this short overview is (1) to clarify the principle of self-assembly of lipidic amphiphilic molecules in an aqueous environment and (2) to present lipidic bicontinuous cubic and hexagonal phases and their current biosensing (with a focus on electrochemical protocols) and biomedical applications.
Keywords: Technology; Cubosome; Liquid Crystals; nanočástice; Nanoparticles; technologie; Lipids; Lipidic cubic phase; Lipidic nanoparticles; Hexosome; Biologically active compounds; kapalné krystaly; lipidy